Muscle mass and estimates of renal function: a longitudinal cohort study. Issue 4 (21st May 2022) - Groothof, Dion; Post, Adrian; Polinder‐Bos, Harmke A.; Erler, Nicole S.; Flores‐Guerrero, Jose L.; Kootstra‐Ros, Jenny E.; Pol, Robert A.; de Borst, Martin H.; Gansevoort, Ron T.; Gans, Reinold O.B.; Kremer, Daan; Kieneker, Lyanne M.; et al.
Abstract: Background: Creatinine is the most widely used test to estimate the glomerular filtration rate (GFR), but muscle mass as key determinant of creatinine next to renal function may confound such estimates. We explored effects of 24‐h height‐indexed creatinine excretion rate (CER index) on GFR estimated with creatinine (eGFRCr ), muscle mass‐independent cystatin C (eGFRCys ), and the combination of creatinine and cystatin C (eGFRCr‐Cys ) and predicted probabilities of discordant classification given age, sex, and CER index. Methods: We included 8076 adults enrolled in the PREVEND study. Discordant classification was defined as not having eGFRCr <60 mL/min per 1.73 m 2 when eGFRCys was <60 mL/min/1.73 m 2 . Baseline effects of age and sex on CER index were quantified with linear models using generalized least squares. Baseline effects of CER index on eGFR were quantified with quantile regression and logistic regression. Effects of annual changes in CER index on trajectories of eGFR were quantified with linear mixed‐effects models. Missing observations in covariates were multiply imputed. Results: Mean (SD) CER index was 8.0 (1.7) and 6.1 (1.3) mmol/24 h per meter in male and female participants, respectively ( P difference < 0.001). In male participants, baseline CER index increased until 45 years of age followed by a gradual decrease, whereas a gradual decrease across the entire range of age was observed in female participants. For a 70‐year‐old male participant with low muscle mass (CER index of 2 mmol/24 h per meter), predicted baseline eGFRCr and eGFRCys disagreed by 24.7 mL/min/1.73 m 2 (and 30.1 mL/min/1.73 m 2 when creatinine was not corrected for race). Percentages (95% CI) of discordant classification in male and female participants aged 60 years and older with low muscle mass were 18.5% (14.8–22.1%) and 15.2% (11.4–18.5%), respectively. For a 70‐year‐old male participant who lost muscle during follow‐up, eGFRCr and eGFRCys disagreed by 1.5, 5.0, 8.5, and 12.0 mL/min/1.73 m 2 (and 6.7, 10.7, 13.5, and 15.9 mL/min/1.73 m 2 when creatinine was not corrected for race) at baseline, 5 years, 10 years, and 15 years of follow‐up, respectively. Conclusions: Low muscle mass may cause considerable overestimation of single measurements of eGFRCr . Muscle wasting may cause spurious overestimation of repeatedly measured eGFRCr . Implementing muscle mass‐independent markers for estimating renal function, like cystatin C as superior alternative to creatinine, is crucial to accurately assess renal function in settings of low muscle mass or muscle wasting. This would also eliminate the negative consequences of current race‐based approaches.